Balancing the images of place Intentional and unintentional place-making by a large infrastructure project: the case of Tangerang LIVE 2020. Issue 4 (1st October 2020) - Delphine,; Witte, Patrick; Spit, Tejo
Abstract : In recent decades, many metropolitan cities have invested in large-scale infrastructure projects to position themselves strategically as competitors in the global economy. Most of these projects visibly transform places by introducing iconic images to reflect the city's global status. One crucial question surrounding these physical changes is how citizens, and particularly communities in the vicinity of the projects, might perceive the transformed place based on their daily practices and individual experiences. Therefore, this article aims to explain the possible conflicts between project promoters and people in the adjacent areas in relation to the creation of place within a large-scale project development through the concept of place-making. The case study is an urban redevelopment project under the branding of Tangerang LIVE 2020, in the Jabodetabek Metropolitan Area in Indonesia. The project is a government's response to globalisation challenges through the creation of a sustainable city. Qualitative in-depth interviews and observations show that the use of large-scale projects as tools for the city's branding strategy have largely contended with people's daily spatial practices, especially because of the failure to provide information to the affected group of people.